IMPROVING THE STUDENTS' READING COMPREHENSION THROUGH THE USE OF SUGGESTOPEDIA METHOD - Adi Chandra; Yuneva Yuneva; Elva Utami (English Education Study Program Faculty of Teacher Training and Education, 2020)
The objective of the research was to get empirical evidenceof the improving students’ reading comprehension of narrative text through suggestopedia method. The method of this research was classroom action research which was conducted in two cycles. The subject of this research was the Second Grade Students of SMA Pesantren Pancasila Bengkulu at Academic Year 2017/2018 with total number of students 18. The research instruments were the observation sheet, interview guidelines, questionnaire and test form. Based on the results of data analysis of pre-test and post-test shown the significant improvement. The average score of pre-test was 54,05. It means two students’ score could pass the KKM. It was 11,11% passed the learning outcome . The average score of post-test 1 was 72,94. It proved that 44,44% students passed KKM. The average score of post-test 2 was 82,77. Then, it was obtained that the percentage of students who could get the score above the KKM in post-test 2 was 100%. Based on the learning activities which have occurred the enhancing from the first to second cycle. From this research findings, it showed that suggestopedia method could improve the students’ reading comprehension of narrative text.